Rola Agencji Nieruchomości Rolnych w przemianach struktury agrarnej w Polsce - Zawojska, Aldona (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2005)
The restructuring and privatisation in Poland's state sector of agriculture was (in 1991) entrusted to the Agricultural Property Agency of the State Treasury (hereafter Agricultural Property Agency). The agency was expected to play an important role in the state agricultural policy as far as structural and ownership transformation of the Polish agriculture is concerned. Almost 80% of land in the Treasury Agricultural Property Stock was taken over from former state-owned farms, asymmetrically concentrated in northern and western provinces. The purpose of liquidation of state farms was intended to strengthen the model of family farms chosen by the Government, mainly through privatisation of state land. In fact, till present the agency has sold merely one third of the land in its stock. The lease remains the dominant form applied in management of land, comprising approximately 2 million ha in permanent use among individual farmers and companies. This paper empirically explores the impacts of AP A on agrarian structure in Poland. The study results show statistically significant strong correlation between regionally distributed property in the form of land sale/land lease and the average area of individual farms.